2022
DOI: 10.3389/fimmu.2022.752215
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of AUF1 in Myeloid Cells Protects From Allergic Airway and Tumor Infiltration and Impairs the Adenosine-Induced Polarization of Pro-Angiogenic Macrophages

Abstract: The four isoforms of the RNA-binding protein hnRNPD/AUF1 have been proposed to limit the use of inflammatory mRNAs in innate immune cells. Mice engineered to lack AUF1s in all tissues are sensitive to acute inflammatory assaults; however, they also manifest complex degenerations obscuring assessment of AUF1s’ roles in innate immune cells. Here, we restricted a debilitating AUF1 mutation to the mouse myeloid lineage and performed disease-oriented phenotypic analyses to assess the requirement of AUF1s in variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In contrast, it was required to switch proinflammatory macrophages towards a proangiogenic phenotype. Their study demonstrated that hnRNPD does not act as a general anti‐inflammatory factorin innate immune cells but has more specialized regulatory effects that allow specific innate immune cell transitions to support tissue infiltration and remodelling processes 36 …”
Section: Role Of Hnrnpd In the Immune Systemmentioning
confidence: 99%
“…In contrast, it was required to switch proinflammatory macrophages towards a proangiogenic phenotype. Their study demonstrated that hnRNPD does not act as a general anti‐inflammatory factorin innate immune cells but has more specialized regulatory effects that allow specific innate immune cell transitions to support tissue infiltration and remodelling processes 36 …”
Section: Role Of Hnrnpd In the Immune Systemmentioning
confidence: 99%